Speaking up on attending ward rounds: a qualitative study of internal medicine residents - Justin J. Choi; Nada Mhaimeed; Peggy Bk. Leung; Jigar H. Contractor; Adrian Majid; Kirana Gudi; William Martinez; Laura Robbins; Martin F. Shapiro (Humanities & Social Sciences Communications, 2024)
Abstract Attending rounds are a core educational component of learning in teaching hospitals. Speaking up in this context has not been explored among medical residents. We aimed to understand residents’ perspectives on speaking up about their own clinical reasoning during attending rounds. This was a qualitative study performed at a single teaching hospital. We selected a random sample of 45 internal medicine residents among 141 in the training program, among whom 21 accepted the invitation to participate. Semi-structured interviews were conducted over Zoom. We performed thematic analysis within a social constructionist epistemology to develop codes, categories, and themes. Analysis continued until thematic saturation was achieved. We interviewed 21 residents, including 9 interns, 7 junior residents, and 5 senior residents. Residents described factors related to team culture, team dynamics, knowledge and experience, domain of patient care, and structure of rounds that influence speaking up during rounds. We identified four themes that were critical for speaking up: (1) promoting a culture of learning; (2) creating psychological safety; (3) developing self-efficacy; and (4) fostering resident autonomy. Feedback from the attending, particularly nonverbal cues perceived as negative, played a prominent role in preventing residents from speaking up. We identified factors for speaking up among residents during attending rounds. Feedback conveyed during attending rounds influenced the culture of learning, psychological safety, and residents’ self-efficacy, which impacted residents’ motivation to speak up. Ward attendings should be mindful of verbal and nonverbal forms of feedback on rounds.